A novel approach for digital image watermarking - Mitashe, Mashruha Raquib; Habib, Ahnaf Rafid Bin; Razzaque, Anindita; Tanima, Ismat Ara (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2016.